An inquiry on the impact of intellectual property rights on foreign direct investments in ASEAN - Lingat, Isabella Ruth C.; Ramin, Ansherina Mei T. (Quezon City School of Economics, University of the Philippines Diliman, 2022)
This study aims to analyze the impact of Intellectual Property Rights (IPR) protection quality on inbound Foreign Direct Investments (FDI) in a panel of 10 ASEAN countries over the period 2000-2020. Using a fixed effects regression model to account for the country-specific effects that may be present due to the existence of country groups, this study found that there is a positive but insignificant effect of IPR quality on the level of FDI inflow. Instead of IPR strength, inflation and GDP were found to have a significant influence on inbound FDI.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: Foreign direct investment -- ASEAN countries; Intellectual property -- Economic aspects -- ASEAN countries; Investments, Foreign -- Government policy -- ASEAN countries; Economic development -- ASEAN countries